2019
DOI: 10.1088/1674-1137/43/2/024104
|View full text |Cite
|
Sign up to set email alerts
|

Description of the critical point symmetry in 124 Te by IBM-2

Abstract: Based on the neutron and proton degrees of freedom, the low-lying energy levels, the E2, M 1 and E0 transition strengths of nucleus 124 Te have been calculated by the neutron-proton interacting boson model. The calculated results are quite consistent with the experimental data. By comparing the key observables of states at the critical point of U πν (5)-O πν (6) transition with experimental data and calculated results, we show that the 124 Te is a possible nucleus at the critical point of the second order phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The B (E2) data of Pd [102][103][104][105][106][107][108][109][110][111][112] and Ru 96-102 nuclei were examined [12][13][14]. Several vibrational-gamma soft properties IBM calculations have been reported that dealt with the IBM and IVBM models [15][16][17][18][19]. The aim of the present work is to interpret the collective behavior of yrast state of 124 Te nucleus by D-G, IBM-1, BM, and IVBM models.…”
Section: Introductionmentioning
confidence: 99%
“…The B (E2) data of Pd [102][103][104][105][106][107][108][109][110][111][112] and Ru 96-102 nuclei were examined [12][13][14]. Several vibrational-gamma soft properties IBM calculations have been reported that dealt with the IBM and IVBM models [15][16][17][18][19]. The aim of the present work is to interpret the collective behavior of yrast state of 124 Te nucleus by D-G, IBM-1, BM, and IVBM models.…”
Section: Introductionmentioning
confidence: 99%